1989
DOI: 10.1021/cm00005a004
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth and phase selectivity of organic superconductors [.beta.-(ET)2I3 (Tc = 1.5 K) and .kappa.-(ET)2Cu(NCS)2 (Tc = 10.4 K)] on graphite electrodes

Abstract: In the past, thin films of ceramic materials including boron nitride have been prepared primarily by vapor deposition techniques.l These films are adequate for some applications; however, they vary a great deal in quality and purity., To achieve several advanced materials goals that Present address: Scientific Rasearch Laboratories, Room E3172, Ford Motor Co., Dearborn, MI 48121-2053.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Previous studies of the electrocrystallization of (ET) 2 I 3 salts have demonstrated that the choice of electrocrystallization conditions influences the selectivity toward the α and β polymorphs, with the kinetically favored α-phase forming at high overpotentials and the thermodynamically favored β-phase forming at low overpotentials . Furthermore, electrocrystallization on electrochemically etched HOPG favors formation of the α-phase, whereas the β-phase forms on pristine HOPG surfaces . Electrochemical parameters also influence polymorph selectivity during growth of the ET x (ReO 4 ) y salts.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of the electrocrystallization of (ET) 2 I 3 salts have demonstrated that the choice of electrocrystallization conditions influences the selectivity toward the α and β polymorphs, with the kinetically favored α-phase forming at high overpotentials and the thermodynamically favored β-phase forming at low overpotentials . Furthermore, electrocrystallization on electrochemically etched HOPG favors formation of the α-phase, whereas the β-phase forms on pristine HOPG surfaces . Electrochemical parameters also influence polymorph selectivity during growth of the ET x (ReO 4 ) y salts.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that the presynthesis treatments of the electrode, such as polishing with fine sand paper and electrolysis in 1 M H 2 SO 4 solution, can lead to different crystalline phases (polymorphism). 26 The choice of the electrolysis solvent is limited by its ability to dissolve both the organic donor and the electrolyte. 21 For this purpose, a mixture of two or more solvents may be required, but one must keep in mind that ultimately the salt of the electro-oxidized species must not be soluble if it is to crystallize.…”
Section: Electrocrystallization: the Experimentsmentioning
confidence: 99%
“…A platinum wire is used as the working electrode. It has also been shown that the presynthesis treatments of the electrode, such as polishing with fine sand paper and electrolysis in 1 M H 2 SO 4 solution, can lead to different crystalline phases (polymorphism) . The choice of the electrolysis solvent is limited by its ability to dissolve both the organic donor and the electrolyte .…”
Section: Electrocrystallization:  the Experimentsmentioning
confidence: 99%
“…Our laboratory recently reported the electrochemical synthesis, on HOPG electrode substrates, of crystalline monolayers based on the charge-transfer salt bis(ethylenedithiolo)tetrathiafulvalene triiodide, (ET) 2 I 3 . , Real-time in situ atomic force microscopy (AFM) revealed that because of epitaxial interactions between the monolayers and the HOPG substrate, monolayer growth initiated by electrochemical oxidation of ET in the presence of triiodide occurred exclusively on pristine terraces instead of at step edges that decorated the HOPG surface. Two monolayer structure types with the same composition were observed, one mimicking the (001) plane of β-(ET) 2 I 3 (Type I) and the other resembling a slightly expanded form of the (1̄10) plane of β-(ET) 2 I 3 (Type II).…”
Section: Introductionmentioning
confidence: 99%